Pelatihan Mengendalikan dan Mengontrol Emosi Bagi Terapis Profesional - Kuswidyaningrum N.J1; Sofia Daniati; Ani Tias Sinora; Jesicka Puspita Sari (ABDI KARYA : Pengabdian Kepada Masyarakat, 2026)
The success of therapy and spa services is greatly influenced by the therapist's ability to manage and control their emotions while providing services. Emotions that are not managed properly can lead to a decline in service quality, client complaints, and psychological fatigue for therapists. This community service activity was carried out by lecturers from the Ibu Kartini Social Welfare Academy in Semarang at PGOT Mardi Utomo Semarang. The community service activity took the form of training in managing and controlling emotions for professional therapists. The implementation methods included material delivery, interactive discussions, simulations, and practical exercises in emotion control techniques tailored to the participants' needs. The results of the activity showed an increase in participants' understanding of the types of emotions, triggering factors, and the ability to apply emotional control techniques before, during, and after serving clients. This activity made a positive contribution to improving the professionalism of therapists and the quality of service.